Relations between Republic of Korea and United Arab Emirates in Last Quarter of XX—XXI Centuries: from Economic Interaction to Special Strategic Partnership - G. N. Valiakhmetova; I. A. Musinova (Научный диалог, 2021)
The evolution of bilateral relations between the Republic of Korea and the United Arab Emirates (UAE) in the context of the formation of the Middle East direction of Seoul’s foreign policy in the 1980s and 2010s is considered. The author identifies and analyzes a set of factors that contributed to building of a constructive dialogue between South Korea and the Arab monarchies of the Persian Gulf and the Arab world as a whole. A periodization of the history of the development of the Korean-Emirati relations is proposed, a description of its main stages, as well as the legal and institutional foundations of bilateral cooperation is presented. Particular attention is paid to the analysis of the transformation of conceptual approaches, methods and diplomatic tools for promoting the national interests of the Republic of Korea in the UAE. The author reveals the reasons for Seoul’s withdrawal from focusing solely on economic interaction with the UAE and the inclusion of South Korea in the political agenda of the Middle East, as well as the solution of urgent problems of ensuring regional security. The role of the South Korean presidents in strengthening the country’s geopolitical positions in the Middle East is emphasized. It is argued that the establishment of a strategic partnership with the UAE allowed the Republic of Korea to make a breakthrough in the Middle East and create favorable conditions for the integration of the UAE into world political and economic processes as an equal partner.